2018
DOI: 10.5539/ijms.v10n2p28
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review on the Use of Sex Appeal vs Non-Sex Appeal Advertising in the Malaysian Context

Abstract: This research examines the perception of customers towards sex appeal advertising. Effect of sex appeal advertising has to be measure in terms of ABC model of attitude, which are affective, behavioural and cognitive. Through the sex appeal advertising, cultural values, lifestyle and behaviours can be affected. Acceptance of nudity among different gender and religious had been investigated in Malaysia market. Research findings show that Chinese are more likely to accept mild sex-appeal advertising while Muslims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This display of sexuality makes a mark on viewer's memory; however, the name brand and its image can be diluted as the findings of this study demonstrated both males and females noted that nude luxury advertisement are less attractive. Sarpal et al (2015) investigated the impact of sex appeal in advertising on emotions and attitudes. A comparison of female to male respondents revealed negative perception of ads featuring same-sex nudes, however, positive perceptions of ads featuring opposite-sex nudes.…”
Section: Sexuality In Advertisingmentioning
confidence: 99%
See 2 more Smart Citations
“…This display of sexuality makes a mark on viewer's memory; however, the name brand and its image can be diluted as the findings of this study demonstrated both males and females noted that nude luxury advertisement are less attractive. Sarpal et al (2015) investigated the impact of sex appeal in advertising on emotions and attitudes. A comparison of female to male respondents revealed negative perception of ads featuring same-sex nudes, however, positive perceptions of ads featuring opposite-sex nudes.…”
Section: Sexuality In Advertisingmentioning
confidence: 99%
“…It may be due to the lack of practical portraying of their respective bodies. The perception of sex appeal in advertising by different genders is examined in several studies not just in Sarpal et al (2015). Advertisements featuring overt sex appeal produced more negative feelings in women than men.…”
Section: Sexuality In Advertisingmentioning
confidence: 99%
See 1 more Smart Citation